Crashworthiness analysis and optimization of different configurations multi-layered corrugated sandwich panels under crush loading. (October 2021) - Shu, Chengfu; Hou, Shujuan; Zhang, YX; Luo, Yutao
Multi-layered corrugated sandwich panels can be made up of different core shapes, different arrangements, the variable height, and variable thickness in every layer. In this paper, the crashworthiness behaviors of multi-layered corrugated sandwich panels with different configurations, which are controlled by these four factors, are analyzed and compared. The optimal configuration is found by adopting orthogonal experimental design and range analysis method. A novel multi-layered corrugated sandwich structure with functionally graded thickness is proposed and studied and is proved to better structural crashworthiness. First, finite element models of multi-layered corrugated sandwich panels are established and validated by experiment. Then, the effect of the four factors with three levels on crashworthiness is analyzed, and we obtain the main factor and the optimal configuration with the maximum specific energy absorption by using orthogonal experimental design and range analysis method. Finally, parametric studies and multi-objectives optimization of the proposed novel multi-layered corrugated sandwich structure with functionally graded thickness are conducted. The optimization is aimed at maximizing the specific energy absorption and minimizing the initial peak force under crush loading, based on the non-dominated sorting genetic algorithm and response surface method technique. These findings can provide valuable guidelines for the design of multi-layered corrugated sandwich panels with different configurations under crush loading.